2002
DOI: 10.1007/s00405-001-0431-0
|View full text |Cite
|
Sign up to set email alerts
|

Inner ear pressure changes following square wave intracranial or ear canal pressure manipulation in the same guinea pig

Abstract: Inner ear pressure was measured in scala tympani with a micropipette during square wave pressure manipulation of the intracranial compartment and, subsequently, of the external ear canal (EEC) in the same guinea pig. As expected, the combination of the cochlear aqueduct and the inner ear behaves as a low-pass filtering system for intracranial pressure manipulation and as a complementary high-pass system for ear canal pressure manipulation. Time constants for pressure equalization were in the order of seconds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…The dependence on inner ear volume was explained by round window membrane position influencing aqueduct flow resistance (Wit et al 2003). The study also indicated that aqueduct flow resistance does not depend on flow direction, in contrast with evidence from earlier research (Densert et al 1981;Carlborg et al 1982;Thalen et al 2001Thalen et al , 2002.…”
Section: Introductioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The dependence on inner ear volume was explained by round window membrane position influencing aqueduct flow resistance (Wit et al 2003). The study also indicated that aqueduct flow resistance does not depend on flow direction, in contrast with evidence from earlier research (Densert et al 1981;Carlborg et al 1982;Thalen et al 2001Thalen et al , 2002.…”
Section: Introductioncontrasting
confidence: 93%
“…Because it was found that RC is not constant during inner ear pressure recovery after a change of inner ear pressure (Thalen et al 2002), we restricted our analysis to the first part of the recovery curves, immediately following a middle ear pressure step (at t 0 ). A horizontal line was fitted to the part of the measured p i curves preceding t 0 , to obtain a value for p 1 (see Fig.…”
Section: Feijen Et Al: Round Window and Aqueduct Flow 405mentioning
confidence: 99%
“…The frequencies of 2 and 4 Hz used in our experiments are notably below the helicotrema cutoff frequency in guinea pigs (Marquardt et al, 2007 ) and will be filtered out by the helicotrema, preventing BM excitation at these frequencies and damage to the cochlear sensory cells during the RW probe stimulation. The role of the cochlear aqueduct in pressure relief at frequencies 2−4 Hz, used to vibrate the RW in our experiments, should be small because the time constant for inner ear pressure relaxation due to the cochlear aqueduct is in the order of seconds (Thalen et al, 2002 ; Feijen et al, 2004 ). The potential influence of mass and viscosity of a relatively large volume of fluid placed on the RW in our experiments should also be small.…”
Section: Discussionmentioning
confidence: 99%
“…The assumptions (a), (b), and (c) of the pistonphone do not apply to the external auditory canal. Thalen et al (2002) measured the inner ear pressure in the scala tympani with a micropipette during square wave pressure manipulation of the intracranial compartment of a guinea pig, and subsequently, of the external ear canal in the same animal. As expected, the combination of the cochlear aqueduct and the inner ear behaves as a low-pass filtering system for intracranial pressure manipulation and as a complementary high-pass system for ear canal pressure manipulation.…”
Section: Rationalementioning
confidence: 99%